Politics of Impoverishment in Nigeria from 1967 to Present: Fuel to Terrorism and National Insecurity - Ani, Johnmary Kelechi (2014)
The character of leadership in a country often influencies the ship of nation building in that state. Nigeria is one country that is yet to have the blessing of transformational leardership since independence. However, by 1967 when the civil war started, selfishness took-over the ambitions of the war-time leaders and by the end of the war, the country's petty-elite have become conscious of the need to manipulate poverty in order to ensure their grip of power. This work shows how the Nigerian ruling class have exploited the masses and used the army of impoverished citizenry to wage war on the state and its resourses. Hence, when they disbanded each group of these armed men, they easily turned themselves into a network of kidnappers and Boko Haram activists, thereby increasing terrorism and national insecurity in the country. The work called for a change of political behaviour both on the leadership and the citizenry towards building a better as well as safe country. Resumo O caráter da liderança num país frequentemente influencia a construção da nação naquele estado. A Nigéria é um país que mantem uma liderança transformacional desde a independência. No entanto, em 1967, quando a guerra civil começou, o egoísmo assumiu as ambições dos líderes da guerra e, até o final da guerra, a pequena elite do país tornou-se consciente da necessidade de manipular a pobreza a fim de garantir o seu controlo. Este trabalho mostra como a classe dominante nigeriana explorou as massas e usou o exército de cidadãos empobrecidos para travar uma guerra contra o Estado e seus recursos. Assim, quando desmembraram cada grupo desses homens armados, estes facilmente se transformaram numa rede de sequestradores e ativistas do Boko Haram, aumentando assim o terrorismo e a insegurança nacional no país. O trabalho exige uma mudança de comportamento político, tanto na liderança quanto na cidadania, para a construção de um país melhor e mais seguro.